Analisis Pergerakan Indeks Harga Saham Gabungan (IHSG) Sebelum Dan Sesudah Pandemi Covid - Hasan Fahmi Kusnandar; Sri Mulyati; Ai Siti Rohana (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
The research is aimed at analyzing the movement of the Composite Stock Price Index (IHSG) before and after the COVID-19 pandemic March 2019-February period. The data used is the Composite Stock Price Index (IHSG) in Indonesia published by the Indonesia Stock Exchange (BEI). The research method used is quantitative with the type of research is an Event Study, with a Paired T-Test model. The result of this research showa that COVID-19 has a significant effect on the Composite Stock Price Index (IHSG) on the Indonesia Stock Exchange (BEI) for the period March 2019-February 2021.